2007
DOI: 10.1177/8756087907084987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rheological Strain Hardening on Extrusion Blown Film of Polyvinylidene Fluoride

Abstract: In this work the effect of strain hardening on poly-vinylidene fluoride (PVDF) extrusion blown film is investigated. Controlled long chain branching is introduced via a multi-functional initiator to produce two PVDF samples with different molecular weight and chain architecture. The branched samples are compared to two reference resins having identical molecular weight and no chain branching. All samples are characterized by size exclusion chromatography (SEC) coupled with triple detection system comprising a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…They found LDPEs as the most stable resins in the film blowing process for their distinct strain hardening behavior, whereas the HDPEs and LLDPEs were unstable for their narrower molecular weight distribution. Later, Mekhilef et al22 studied the effect of rheological strain hardening on extrusion blown film of polyvinylidene fluoride (PVDF). He observed that the strain hardening of the branched PVDF samples increases the processing window with respect to reference samples (not branched) and allows for the formation of a large and stable bubble, thus producing films with reduced thickness and higher clarity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found LDPEs as the most stable resins in the film blowing process for their distinct strain hardening behavior, whereas the HDPEs and LLDPEs were unstable for their narrower molecular weight distribution. Later, Mekhilef et al22 studied the effect of rheological strain hardening on extrusion blown film of polyvinylidene fluoride (PVDF). He observed that the strain hardening of the branched PVDF samples increases the processing window with respect to reference samples (not branched) and allows for the formation of a large and stable bubble, thus producing films with reduced thickness and higher clarity.…”
Section: Resultsmentioning
confidence: 99%
“…In these cases, the different processability of the polymers may be attributed to differences in molecular architecture due to factors such as branching and/or the presence of a high‐molecular‐weight tails18–20 that are not readily detected in shear but are more visible in extensional deformations. In fact, one of the key properties in extrusion blown film is extensional viscosity 21, 22. Indeed, it is well recognized that bubble stability, biaxial stretching, and thickness uniformity are very sensitive to extensional viscosity.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Also, a small amount of high-molecular-weight fraction containing chain branching might exist resulting from the synthesis of PVDF resins, which could also give a strain hardening typical of branched polymers. 58 A clear mechanism for the strain hardening of PVDF is still unclear for this moment and also not the aim of this study. A i (t) is the area of cross-section perpendicular to film coextrusion direction with A i (t) = W i (t)×H i (t), where W i (t) and H i (t) are the time-dependent width and thickness of a layer i, respectively.…”
Section: Role Of Diffuse Interphase In Extensional Rheological Behavimentioning
confidence: 95%
“…Thus, the modified polymer resisted up to the elongational deformation without failure for the complete test durations. Considering the wide polydispersity for the modified PLA, this gives rise to the assumption that the effect of the branching structure on the strain hardening dominates [28,29]. Depending on the number of branches and molecular weight, entanglement density may be increased or decreased by branching.…”
Section: Uniaxial Extensional Experimentsmentioning
confidence: 99%